PENINGKATAN KEMAMPUAN SISWA SMK MELALUI PELATIHAN PENGELOLAAN DATA HASIL PENGUKURAN DAN PEMETAAN MENGGUNAKAN APLIKASI SURFER 11 - Mulyono, Tri; Purnomo, Adhi (LPPM Universitas Negeri Jakarta, 2022)
Survey and mapping in the Industrial 4.0 era increasingly requires personnel who have the knowledge and skills in data survey management such as the use of the Surfer 11 application. Through community service activities carried out in 2021 with a target audience of Students of the Building Modeling and Information Design Study Program (DPIB) SMKN 1 Cikarang Barat, Kab. Bekasi, West Java Province, whose objectives increasing knowledge and specific are: (1) Introducing DPIB students about processing measurement and mapping data; and (2) providing an understanding of the use of the Surfer 11 application. The method used is in the form of online training with lectures. Evaluation of the success of the program is carried out through pre-test and post-test questionnaires according to the class material. The results of the implementation of the activity were attended by 141 on the first day and 144 on the second day from 156 participants. The results of data collection for evaluation of activities from 50 respondents can be concluded: (1) training participants for the use of the Surfer 11 application from those who do not know to become familiar or know from 70% are reduced to 6%; and (2) his understanding of the Surfer 11 Application showed that from those who did not understand (4 – 8%) to understand to very understand (28 – 54%).